Presence of language-learning opportunities and migration - Matthias Huber; Silke Übelmesser (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper analyses the effect of the presence of German language learning opportunities abroad on migration to Germany. We use information on the presence of the Goethe-Institut (GI), which is an association that promotes German culture and offers language courses and standardized exams. Our unique dataset covers 69 countries for the period 1977 to 2014. In this multiple-origin and single-destination framework, we estimate fixed-effects models as our basic specification. We find evidence that the number of language institutes of the GI in a country is positively correlated with migration from that country to Germany. The correlation is higher for countries with lower income, larger linguistic distance and without wars. To establish causality, we consider Switzerland as an alternative destination country as the decision to open a language institute in a country is exogenous to migration flows from that country to Switzerland. We find that the institutes of the GI also affect migration flows to the German-speaking part of Switzerland, but not to the French- and Italian-speaking part. Backed by further extensions which control for the presence of multilateral resistance and omitted variable bias, we interpret our results as presenting a causal effect from language learning opportunities to migration flows.
Keywords: F22; O15; J61; 330; language skills; language learning; international migration; panel data